A method for the dynamic range extension of a pixelated Silicon detector beam profilometer based on the incomplete reset mechanism. (8th March 2017) - Caccia, M.; Santoro, R.; Antonello, M.
Abstract: The SUCIMA collaboration, within a project supported by the European Commission in the Fifth Framework Program, developed a sensor for non-disruptive real-time beam profilometry for hadron therapy centres. The sensor, named MIMOTERA, has been used at different European facilities, imaging beams by direct impact on the sensor and by the detection of secondary electrons emitted by thin targets. In 2015, the detector has been thinned to 50 μ m, integrated in a high vacuum and cryogenic temperature compliant assembly and successfully commissioned as antiproton beam monitor for the AE ḡ IS experiment at CERN. The detector contributed to the optimisation of the experiment functionality providing the shape and position of the beam on a spill-by-spill basis. However, it failed in measuring the fluctuations of the beam intensity because the deposited energy exceeded the full well capacity and saturated the output signal. In order to recover this information, a method was developed based on the persistence of the signal in a series of frames that follows the one corresponding to the beam impact, due to the incomplete sensor reset. A laboratory test that makes use of a laser with tuneable intensity was designed and the method was qualified. This paper reports the description of the procedure and the main outcomes.